2014
DOI: 10.1371/journal.pntd.0002832
|View full text |Cite
|
Sign up to set email alerts
|

Species-Directed Therapy for Leishmaniasis in Returning Travellers: A Comprehensive Guide

Abstract: BackgroundLeishmaniasis is increasingly reported among travellers. Leishmania species vary in sensitivity to available therapies. Fast and reliable molecular techniques have made species-directed treatment feasible. Many treatment trials have been designed poorly, thus developing evidence-based guidelines for species-directed treatment is difficult. Published guidelines on leishmaniasis in travellers do not aim to be comprehensive or do not quantify overall treatment success for available therapies. We aimed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 214 publications
1
74
0
Order By: Relevance
“…To date an ideal anti-leishmanial agent is far from being discovered; its desirable features would be effectiveness, safety, ease of administration, and affordability. The recent paper by Hodiamont et al demonstrates the lack of evidence in the literature for treatment of several clinical categories with different Leishmania species [131]. The choice of treatment is influenced by previous experience as well as availability of a particular drug within a country.…”
Section: Leishmaniasis Patterns Treatmentmentioning
confidence: 99%
“…To date an ideal anti-leishmanial agent is far from being discovered; its desirable features would be effectiveness, safety, ease of administration, and affordability. The recent paper by Hodiamont et al demonstrates the lack of evidence in the literature for treatment of several clinical categories with different Leishmania species [131]. The choice of treatment is influenced by previous experience as well as availability of a particular drug within a country.…”
Section: Leishmaniasis Patterns Treatmentmentioning
confidence: 99%
“…5 Local treatment with intralesional pentavalent antimony (PA) is considered the first-line therapy of CL caused by L.tropica unless there are multiple (>5), large (>4 cm) or disfiguring facial lesions. 6,7 In such cases, systemic treatment with intravenous PA or L-Amb, oral miltefosine or oral imidazoles is recommended. 8 Intravenous PA is most commonly used, but it requires long hospitalization and has potential severe sideeffects.…”
mentioning
confidence: 99%
“…8 Intravenous PA is most commonly used, but it requires long hospitalization and has potential severe sideeffects. 6 In a recent retrospective study of 70 children with CL caused by L. tropica, efficacy and safety of intravenous PA and L-Amb were evaluated; the authors observed a superior cure rate and a shorter hospitalization period with L-AmB, proposing L-AmB as the first-line systemic therapy. 9 L-AmB is welltolerated, being is its high cost the main drawback.…”
mentioning
confidence: 99%
“…In travelers returning from endemic areas, the combination of intralesional antimony with cryotherapy is recommended for the treatment of uncomplicated cutaneous leishmaniasis, except for L. guyanensis and L. braziliensis infections in which parenteral therapy is preferred [22].…”
Section: Discussionmentioning
confidence: 99%